The Influence of UPL-UKL Obedience to the Quality of the Physical Environment in the Hospital, Clinic and the Maternity Home at Mojokerto - Handoko, Trio; Indasah; Koesnadi (Journal for Research in Public Health, 2020)
Business activities in the health field can provide the positive and negative impact on the environment both physical and non physical. to minimize the impacts resulting from these efforts, so any initiator is required to make environmental feasibility document (UKL-UPL). But the fact that happen the proponent to implement document obedience UKL-UPL is still very low. Report on the monitoring and management of the environment should be done every 6 months by healthcare agencies such as hospitals, clinics and maternity homes, still has not been made by some health service agencies. The purpose of this research was to analyze the influence of UKL-UPL obedience to the quality of the physical environment in the hospital, clinics and maternity homes Mojokerto.This research design are analytic observational with quantitative approach. Research variables are UKL-UPL obedience as the independent variable and the quality of the physical environment as the dependent variable. The population of the research that is all of health service Agencies in Mojokerto as much as 39 establishments. Samples taken by random sampling technique as much as 36 respondents. Data is collected with ceklist instruments and processed in coding, editing, tabulating and scoring as well as tested with logistics regression test.Logistic regression results indicate that partially and simultaneously the value of p values < 0.05 so that that there were influences of UKL-UPL obedience to the quality of the physical environment in the hospital, clinics and maternity homes, Mojokerto and the simultaneous influence of 50%.The presence of disobedience committed by agencies of the Ministry of health related water management water management, waste management and clean B3 can affect the quality of the physical environment the health service agencies. Management is expected to carry out the management and monitoring of the environment with good and right so as to reduce the risk of transmission of disease occurrence in the environment of the place of work.